The permanently rotating wind turbines: a new strategy for reliable power system frequency support under low and no wind conditions - Džodić, Kristina; Đurišić, Željko (Frontiers in Energy Research, 2023)
The problem of frequency stability becomes more concerning as the presence of converter-interfaced units increases and conventional generators are suppressed. A decrease in total system inertia, inherently delivered by synchronous generators, results in abrupt frequency changes and jeopardizes power system stability. Therefore, securing sufficient flexible resources with frequency support capability is necessary. This paper proposes using wind turbines under no wind conditions as frequency-responsive flywheels. The wind turbine's converter management allows rotating speed control, fast power injection, and release of the turbine's stored kinetic energy even when no wind energy is available. The estimated accessible kinetic energy in the wind turbine justifies the proposed concept, and the energy consumption due to flywheel operation is shown to be acceptable based on several commercial wind turbine data. A case study is performed for the South Banat region in Serbia to demonstrate the presented management concept. Additionally, a dynamic simulation was implemented to illustrate the continuous operation strategy's impact on frequency stability in a low-inertia system under low and no wind conditions. Besides virtual inertia continuous capability, the proposed concept provides reduced wear of the wind turbine mechanical components due to a lower number of on/off events.